Geography teachers' views on effective geography teaching - (:unkn) unknown (Eyup Artvinli, 2017)
Geography teaching is fulfilled within the frame of a specific curriculum and in order to achieve some acquirements in Turkey. Though there are course books prepared in accordance with the curriculum and activities in order to achieve the acquirements in geography teaching, they are geography teachers who will coordinate and fulfill the curriculum and achieve the terminal behavior defined as education. A qualitative method has been used in order to examine the teachers' effectiveness in geography teaching. In three different types of high school, 19 geography teachers were interviewed using a semistructured interview form prepared by the researchers. During the interview, the researchers asked the teachers some questions about their teaching methods, teaching techniques and materials used, skills provided, classroom management, and developments made through in-service training. The data acquired were evaluated through content analysis and some categories were formed. According to the findings, it is seen that the geography teachers are effective in education and training. According to the results obtained from the research, it is determined that the geography teachers use the materials, methods and techniques in accordance with the curriculum. In addition, it is seen that they participate in the in-service training in order to develop and maintain the effective teaching. © RIGEO 2017.
Keywords: Curriculum; Effective teaching; Geography teacher; Qualitative study; Teaching geography